Decalintetracids A and B, two pairs of unusual 3-decalinoyltetramic acid derivatives with phytotoxicity from Fusarium equiseti D39. (May 2022) - Zhao, Dong-Lin; Liu, Jing; Han, Xiao-Bin; Wang, Mei; Peng, Yu-Long; Ma, Si-Qi; Cao, Fei; Li, Yi-Qiang; Zhang, Cheng-Sheng
Abstract: The filamentous fungi Fusarium sp. are well-known for their ability to produce abundant specialised metabolites with attractive chemical structures and bioactivities. In this study, chemical analyses of the endophyte F. equiseti D39 led to the isolation and identification of two pairs of undescribed 3-decalinoyltetramic acids (3DTAs) E/Z diastereomers, decalintetracids A and B. Their structures were elucidated by comprehensive spectroscopic analysis and quantum-chemical calculations. Although 3DTAs were commonly reported from fungi, decalintetracid A possessed an unprecedented tricyclo [7.2.1.0 2, 7 ] dodecane skeleton, which added the diversity of these fungal metabolites. In addition, decalintetracid B was featured by a unique 6/6/5 ring system core. A plausible biosynthetic pathway for decalintetracids A and B was proposed. Both compounds exhibited phytotoxicity toward Amaranthus retroflexus L. and Amaranthus hybrid, indicating their potential as natural herbicides. Graphical abstract: Image 1 Highlights: Two pairs of undescribed 3DTA derivatives were isolated from Fusarium equiseti D39. Decalintetracid A has an unprecedented tricyclo [7.2.1.0 2, 7 ] dodecane skeleton. Decalintetracid B was featured by a unique 6/6/5 ring system core. The two compounds showed phytotoxicity toward A. retroflexus L. and A. hybrid.